An integrated OADM based on Bragg trans-reflectance in 1550 nm VCSEL optical fibre access networks - Boiyo, D.K.; Kipnoo, E.K. R.; Gibbon, T.B. (Elsevier, 2018)
We experimentally demonstrate an all passive OADM using a single BGF, a pair of optical circulators and the low cost and energy efficient VCSELs. In this study, double reflection due to Bragg effect on a single fibre grating has been used to create drop and add multiplexers at 1549.9 nm wavelength with 31.4 dB wavelength isolation ratio. In performance evaluation at the 10−9 BER threshold level, a 0.3 dB add and drop receiver penalty for a 8.5 Gb/s data signal is incurred while a 0.8 dB transmission penalty is incurred for ∼25.5 km fibre distance. Using optical trans-reflectance, this paper, provides a less costly and less power consuming channel management using OADMs for high speed VCSEL transmission.